2020
DOI: 10.1111/pan.14021
|View full text |Cite
|
Sign up to set email alerts
|

An approach to using pharmacokinetics and electroencephalography for propofol anesthesia for surgery in infants

Abstract: Propofol-based total intravenous anesthesia (TIVA) is gaining popularity for pediatric surgical procedures. 1 While TIVA has been popular for many years in adult ambulatory surgery and pediatric radiological imaging, inhalational anesthesia has remained the mainstay for pediatric surgical anesthesia, especially in infants. Nevertheless, TIVA is the preferred technique for selecting infant surgical populations, including those at risk of malignant hyperthermia or emergence delirium and those requiring neurophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…, EEG features, sevoflurane and propofol pharmacokinetics). 11–13 A consecutive sampling approach was performed. After screening for eligibility, the patient family or caregiver was approached preoperatively to obtain written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, EEG features, sevoflurane and propofol pharmacokinetics). 11–13 A consecutive sampling approach was performed. After screening for eligibility, the patient family or caregiver was approached preoperatively to obtain written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The Pediatric Quality of Life questionnaire is a validated and widely used instrument in pediatric research (translated into more than 50 languages) that assesses physical, emotional, and social functioning in children and infants. 20,21 The instrument consists of questions in the following age groups: 1 to 12 months, 36 questions divided into Physical Functioning (6), Physical Symptoms (10), Emotional Functioning (12), Social Functioning (4), and Cognitive Functioning (4); 13 to 24 months, 45 questions divided into Physical Functioning (9), Physical Symptoms (10), Emotional Functioning (12), Social Functioning (5), and Cognitive Functioning (9); and 25 to 36 months, 24 questions divided into Physical Functioning (8), Emotional Functioning (5), Social Functioning (5), and Cognitive Functioning (6). Each question is scored on a 5-point Likert scale.…”
Section: Pediatric Quality Of Life Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The specific meaning of each index is shown in Figure 2 . The recommended SEF range for the maintenance of general anesthesia is 10–15 in children [ 12 , 30 , 35 ]. The EtSevo should be immediately changed when SEF < 10 and DSA images show burst suppression (black vertical segment) and main power frequency band (red horizontal band) depression; when the EEG waveform presents burst suppression, and isoelectric and other conditions, indicating that the depth of anesthesia may be abnormal; or when the vital signs of the child show serious fluctuations.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Xu et al reported that the SEF, DSA, and raw EEG could be more effective for reflecting anesthetic depth than proprietary indices (e.g., BIS, Narcotrend index, and Patient State Index (PSI)) in pediatric surgery [ 12 , 30 ]. Other studies also reported that the SEF could be more effective in representing anesthetic depth [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%